In Vitro Shoot Multiplication In Chrysanthemum morifolium Ramat - Mohamed, seifeldin Ali (Gezira Journal of Agricultural Science, 2023)
This study was conducted to evaluate the effect of explant type (shoot tips and lateral buds); different concentrations of the cytokinin 6-Benzyl amino purine (BAP) at 1, 2, 4, 6, 8 mg/l; the organic acid (ascorbic acid) at 20 and 40 mg/l; the amino acid L-glycine at 30 and 60 mg/l; liquid medium overlay onto solid media (0, 4, 8, 12, 16 ml of liquid medium)  and light intensity (0, 1.4, 7, 14 µmol m -2 s -1 ) on in vitro shoot multiplication in Chrysanthemum morifolium . The completely randomized design was used in these experiments. The multiplication parameters collected were number of shoots, shoot length, number of leaves and number of nodes. Data were subjected to analysis of variance. Means were separated by Duncan’s multiple range test, and T-test. Results showed no significant difference in multiplication measurements between shoot tips and lateral buds. Significant differences were recorded as a result of BAP concentrations. The low concentrations of BAP significantly stimulated multiplication parameters. The supplement of ascorbic acid significantly enhanced multiplication at low concentration. Incorporation of L-glycine at the concentration of 30 or 60 mg/l in the medium enhanced multiplication significantly compared to the control. Addition of liquid medium onto the surface of solid medium  stimulated all growth parameters significantly. Cultures incubated under dark condition resulted in significant increase in multiplication but the resultant shoots exhibited clear symptoms of etiolation.